Anthelmintic resistance in small ruminant parasites: Implications for smallholders in Southeast Asia - Hood, G.M. (Australian Centre for International Agricultural Research, 2004)
This chapter reviews the current status of anthelmintic resistance in Southeast Asia, and examines the implications for smallholders, for whom anthelmintics offer one key to the control of parasitism and the development of enterprises based on small ruminants. Alternatives to the use of anthelmintics such as nutritional strategies and grazing management are also considered, since these have significant potential for reducing the selection pressure for anthelmintic resistance. Topics addressed in this chapter include tests for, prevalence of, risk factors & transmission of - anthelmintic resistance; traditional tethering; stall-feeding; and extensive grazing systems.